Students Perceptions Related to The Interaction Between Teachers and Students in The Learning Process - Yohana Satinem; Yeni Asmara; Selpia; Regita Nada Hervanis; Agus Susilo (Edutech Publishing Media, 2023)
The purpose of this study was to determine student perceptions related to interactions between teachers and students in the learning process. The problem of this research is the interaction between teachers and students in the process of implementing learning, which is done so that student perceptions related to interactions between teachers can trigger a learning process well, so as not to cause failure for the teacher when implementing learning. In the learning process, the interaction between teachers and students greatly affects students' interest in learning, in which the teacher plays an important role during the learning process. The research method is about the basis for conducting research related to student perceptions regarding the interaction between teachers and students in the learning process. The design of the author of this scientific work with a qualitative research study based on literature review. Analysis of sources obtained comes from relevant journal sources and reference books. Results and discussion, namely the interaction between teachers and students in the learning process. Student response or acceptance is related to an action taken between the teacher and students so that students can understand an important interaction concept in learning. The existence of an interaction carried out by a teacher towards students can make students become brave and confident to communicate (express opinions) such as during discussions, questions and answers, quizzes and rewards. The interaction between teachers and students in the learning process must be equally active. An affectionate and conducive atmosphere that is successfully built in a relationship will make a person able to direct the interaction in a positive direction. This concept is very important and relevant not only to the concept of education today but also to education in the future.